The Relationship Between Sleep Duration and Participation in Home, School, and Community Activities Among School-Aged Children - Chien, Chi-Wen; Cheung, Pauline; Chen, Chao-Ying (Frontiers in Neuroscience, 2019)
Sleep duration has important implications for children’s participation in daily activities; however, past attempts to examine this relationship has been limited to specific types of physical or educational activities. The present study aimed to investigate the relationship between sleep duration and participation in various daily activities among school-aged children. A school-based sample of 391 children aged 5–12 years (boys: 52.4%) participated in this cross-sectional survey. Sleep duration was quantified using parental reports of their children’s bedtime and wake-up time on weekdays and weekends. The parent-reported Participation and Environment Measure for Children and Youth was used to measure their children’s participation frequency and involvement in 25 home, school, and community activities. The results of hierarchical regression analyses showed that, when the demographic variables were controlled for, weekday sleep duration was positively related to homework involvement and negatively related to the frequency of TV viewing; however, it was unrelated to participation in school and community activities. Conversely, weekend sleep duration was positively related to overall participation in school activities, and participation frequency and involvement in some home and community activities. Furthermore, sleep duration was approximately an hour shorter on weekdays than on weekends. These results suggest that weekend sleep duration has stronger positive implications for children’s participation in daily activities than does weekday sleep duration. Interventions aiming to promote children’s activity participation may either prolong children’s weekend sleep duration or address their shorter weekday sleep duration.